The growth, development and modification of barley seed crops - Chatham, Catherine J. (1985)
A series of field and growth room experiments on winter barley (Hordeum vulgare) L. syn. H. sativum Jessen) were undertaken between 1980 and 1983 at the University of Nottingham School of Agriculture, Sutton Bonington. The aim of this study was to attempt to elucidate those factors which influence the suitability of harvested grain for use as seed. Density, nitrogen fertilizer (both rate and timing) and plant growth regulator applications were used to modify crop growth and development with a view to enhancing the suitability of the grain for seed purposes. It has been shown that the final grain yield and yield components could be manipulated by the judicious use of the inputs examined. However yield component modification was dependent upon the variety used. Consistent increases in seed yield as a result of the husbandry inputs were not always detectable but where alterations to crop growth and development did occur this occasionally resulted in a reduction in total grain yield. None of the PGRs applied significantly or consistently influenced the suitability of the grain for seed purposes. All nitrogen trials were conducted on Index 0 nitrogen sites. However the residual nitrogen may have differed between sites and seasons so confounding the effects of nitrogen treatments. Alterations of both nitrogen rate and timing can be used to modify crop growth patterns. Alteration of sowing density resulted in a change in the grain yield components. Increased sowing density resulted in an increase in total ear number with a concomitant reduction in mean grain number per year. As grain yield was shown to be correlated with grain number per unit area the modification of these two components by sowing density did not necessarily influence final grain yield because of yield component compensation. The seed industry is still divided in its attitude to the desirability or necessity of size graded seeds. However if more emphasis is placed on the production of cereal seed crops the work reported here will help to clarify the possible outcome of desirable modifications to the growth and development of the winter barley crop for seed.